Epidemiological assessment of the most common cancers among urban and rural male populations - A. V. Vazhenin; S. V. Novikova; Yu. A. Tyukov; A. A. Kotov (Сибирский онкологический журнал, 2022)
According to the who data, lung cancer (lc) is the most common cancer (nearly 13,0 %) and prostate cancer (pc) is the second most common cancer (11,0 %) in men worldwide. In the chelyabinsk region, pc has been the most common cancer since 2019, accounting for 18,3 % of all cancer cases in males, and lc has become the second most common cancer, accounting for 6,8 %.The purpose of the study was to evaluate the epidemiological situation in terms of the most common cancers (lc and pc) in a male population of rural municipal areas in the constituent entity of the Russian Federation.Material and methods. The incidence and mortality of lung and prostate cancers were analyzed in 1020 males from five rural municipal districts of the chelyabinsk Region, territorially included in the magnitogorsk oncological cluster. Data were obtained from the population cancer Registry of the chelyabinsk Region for 2010–2019.Results. Over a ten-year period, the average detection rates for lc and pc were 103.59 ± 3.28 and 50.75 ± 4.86, respectively per 100,000 men in rural municipal areas. The average 1-year mortality rates from lc and pc were 59.33 ± 2.14 % and 21.11 ± 2.89 %, respectively. The average overall lc mortality was 85.44 ± 5.1 deaths per 100,000 men and the average overall pc mortality was 23.04 ± 1.26 deaths per 100,000.Discussion. The rates of the 1-year mortality from lc and pc, as well as the rates of the overall mortality from lc in men of rural municipal areas were higher than those in urban areas, demonstrating the tendency to increase.Conclusion. To ensure access to oncology medicine for patients in rural areas, private medical oncology clinics are involved on the basis of public-private partnership.